The stability of soil aggregates in sweet cherry (Prunus avium L.) orchards of different ages and varieties - Muhao Chen; Shu Feng; Jun Wang; Mingyu Gao; Min Liu; Kaibo Wang; Zhou-ping Shangguan; Yongwang Zhang (Heliyon)
In recent years, Sweet Cherry (Prunus avium L.) have been in high demand and planted in large quantities due to their nutritional value and appealing organoleptic properties. The management mode and species characteristics in the tillage process lead to a decrease in soil quality, and the stability of soil aggregates and decrease in soil nutrients indicate this. However, the effects of different sweet cherry varieties and increasing planting ages on soil quality remain unknown. In this study, soil samples were quantitatively analyzed at different soil depths (0–20 cm, 20–40 cm, 40–60 cm) in cheery orchards of different varieties and ages. The results demonstrated that the particle size content of soil aggregates differed among the varieties of sweet cherry in different soil layers. The mechanical stability of soil aggregates was found to be the lowest in Jimei cherry orchard, where the mass ratio of aggregates with particle sizes exceeding 0.25 mm (R > 0.25) was below the highest 20.99 %, geometric mean diameter (GMD) was below 22.52 %, and mean weight diameter (MWD) was below 17.46 %. In contrast, lower ages demonstrated superior performance in aggregate water stability. The stability of soil aggregates was found to be affected by sweet cherry cultivation, with changes observed in the content of SOC and TN in the surface soil. Principal component analysis indicated that soil quality deteriorated increasingly with ages, while pass-through analysis demonstrated that ages and soil aggregate stability were key factors influencing soil quality. In conclusion, in addition to economic benefits, soil quality should also be protected. This study can help to improve the scientific theoretical basis for the introduction of sweet cherry planting on the Loess Plateau and the management of soil quality.